PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO (STUDI PADA KONSUMEN SMARTPHONE OPPO DI AAN CELL KALIWUNGU KENDAL) - Setyani Nur Afifah; Rokh Eddy Prabowo (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
The purpose of this study is to analyze the influence of each of the free variables of product quality, brand image, and price perception on purchasing decisions as bound variables. The population in this study were Oppo smartphone buyers at AAN Cell Kaliwungu Kendal. Primary data were obtained using questionnaires while secondary data using literature studies. The sampling method was carried out using purposive sampling techniques with a total sample of 100 peope. Based on the resuls of SPSS version 24.0 shows, that the test of the research instrument shows, that all indicators are valid and all variables are reliable. Based on the F test, it shows that all free variables silmutanly affect purchasing decisions. Based on the results of the regression coefficient and t test, it shows that product quality variables have a positive and significant effect on purchasing decisions, brand image variables have a positive and significant effect on purchasing decisions, brand image variables have a positive and significant effect on purchasing decisions, and price perception variables have a positive and significant effect on purchasing decisions.